The Role of Language in Cognitive Development in the Hard of Hearing - Radhika S (Journal of All India Institute of Speech and Hearing, 1970)
A group of twentysix hard of hearing children in the age range 4 years. 7 months to 8 years. 6 months were studied for their performance on the "MysoreCognitive Capabilities Test (T. Padmini, 1979). Eleven children were included in Group A (oral group), four older cildren in Group A (oral group) and elevenchildren in Group B (total communication group). Histroy relevant to each child was collected from the parents or family members or the records. The resultsof the study were compared with the classical finding of Jean Piaget on normal hearing children. A comparison both qualitative and quantitative between GroupA and Groups B on the three mental operational tasks of seriation, classification and conservation from the Mysor Cognitive Capabilities test was done.